Access to long-term care: perceptions and experiences of older Dutch people. (8th June 2015) - Schipper, Lisette; Luijkx, Katrien G.; Meijboom, Bert R.; Schalk, René; Schols, Jos M.G.A.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Despite the current focus on demand-based care, little is known about what clients consider important when they have a request for formal long-term care services. The paper aims to discuss this issue. Design/methodology/approach – Questions about the access process to care services were added to the "Senior Barometer", a Dutch web-based questionnaire that assesses the opinion of older people about different aspects in life. The questionnaire surveyed both people who already requested care services ("users"), and people that did not ("future clients"). Findings – The results show a significant difference in what people expect to be the first step from what users actually did, when requesting formal care services. In addition, there was a significant difference on how "users" and "future clients" rated several access service aspects. Research limitations/implications – The results give valuable information on how both "users" and "future clients" value the access process. The findings also provide valuable input for organizations providing long-term care for older clients about the important issues that have to be considered when organizing the access process. Originality/value – This study shows what older people in the Netherlands find important during the access process to care and this has not been explored before. The difference between what "users" and "future clients" find of importance in the care access process suggests that it is difficult for people to foresee what will be important once the need for care arrives, or where they will turn to with a request for care services.